Comparison of wear properties of Ti6Al4V fabricated by wrought and electron beam melting processes in simulated body fluids. Issue 5 (30th January 2020) - Xiang, Dingding; Tan, Xipeng; Liao, Zhenhua; He, Jinmei; Zhang, Zhenjun; Liu, Weiqiang; Wang, Chengcheng; Shu, Beng Tor
Abstract : Purpose: This paper aims to study the wear properties of electron beam melted Ti6Al4V (EBM-Ti6Al4V) in simulated body fluids for orthopedic implant biomedical applications compared with wrought Ti6Al4V (Wr-Ti6Al4V). Design/methodology/approach: Wear properties of EBM-Ti6Al4V compared with Wr-Ti6Al4V against ZrO2 and Al2 O3 have been investigated under dry friction and the 25 Wt.% newborn calf serum (NCS) lubricated condition using a ball-on-disc apparatus reciprocating motion. The microstructure, composition and hardness of the samples were characterized using scanning electron microscopy (SEM), x-ray diffraction and a hardness tester, respectively. The contact angles with 25 Wt.% NCS were measured by a contact angle apparatus. The wear parameters, wear 2D and 3D morphology were obtained using a 3D white light interferometer and SEM. Findings: EBM-Ti6Al4V yields a higher contact angle than the Wr-Ti6Al4V with the 25 Wt.% NCS. EBM-Ti6Al4V couplings exhibit lower coefficients of friction compared with the Wr-Ti6Al4V couplings under both conditions. There is only a slight difference in the wear resistance between the Wr-Ti6Al4V and EBM-Ti6Al4V alloys. Both Wr-Ti6Al4V and EBM-Ti6Al4V suffer from similar friction and wear mechanisms, i.e. adhesive and abrasive wear in dry friction, while abrasive wear under the NCS condition. The wear depth and wear volume of the ZrO2 couplings are lower than those of the Al2 O3 couplings under both conditions. Originality/value: This paper helps to establish baseline bio-tribological data of additively manufactured Ti6Al4V by electron beam melting in simulated body fluids for orthopedic applications, which will promote the application of additive manufacturing in producing the orthopedic implant.